Adoption and implementation of new technologies in hospitals: a network perspective. Issue 2 (17th May 2018) - Mikhailova, Olga
Abstract : Purpose: The purpose of this paper is to address challenges and opportunities that smaller hospitals with limited resources may face when they are adopting and implementing innovative technologies. Design/methodology/approach: Based on a single case study with interviews and document analysis, this paper focuses on the recombination of resources, actors and activities during the process of technology adoption and implementation at a Danish hospital. Theoretically, it takes an interaction perspective for exploring the interplay between inner and outer networking during the innovation processes. Findings: This study illustrates how the adoption and implementation of advanced medical technology requires significant investment, which is particularly burdensome for smaller hospitals. Constrained by limited resources, they have to develop creative combinations of resources through negotiation and embrace collaborative approaches to join and sustain themselves in the user-producer network. Originality/value: This paper contributes to the innovation field by suggesting ways in which practitioners at smaller hospitals can align with technology providers' strategies and succeed by positioning their hospitals in relation to extended user-producer networks. This study further emphasizes the necessity of a broader discussion regarding the importance of user-producer interactions during innovation processes in health care settings.